Adsorption behavior of Cr(VI) by biomass-based adsorbent functionalized with deep eutectic solvents (DESs) - Qian Li; Qing Huang; Xin Ya Pan; Hang Yu; Zi Tong Zhao (BMC Chemistry, 2022)
Abstract This study was aimed to evaluate the performance of DESs functionalized peanut shell (PSD) as biosorbent for removing Cr(VI) from water. The effects of pretreatment, initial concentration, adsorption temperature, kinetics, adsorption isotherm, and thermodynamics were investigated. Scanning electron microscopy (SEM) and Point of Zero charge (pHpzc) techniques were used for characterization of the adsorbents. The results showed that the rigid structure of peanut shell was broken down after DESs modification and the point of zero charge was 6.02 for peanut shell and 6.84 for PSD, which exhibited a slightly acid character. Based on the comparisons of linear and nonlinear analysis of four kinetic models and four isotherms, the pseudo-second-order kinetic model was found to be suitable for describing the adsorption process. The presence of a boundary effect was observed within the range of research, indicating that internal diffusion was not the only rate-controlling step. The equilibrium data were well represented by the Langmuir model rather than the Freundlich, Temkin, and Dubinin–Radushkevich models. The maximum capacity derived was 5.36 mg g−1. Changes in Gibb’s free energy, enthalpy, and entropy revealed that Cr(VI) adsorption onto modified peanut-shell powders was a spontaneous and endothermic process. However, the highest desorption efficiency was only 8.77% by using NaOH as a desorbing agent. Graphical abstract